Correlates of mobile screen media use among children aged 0-8: Protocol for a systematic review - Paudel, S.; Leavy, J.; Jancey, Jonine (2016)
Background: Childhood is a crucial period for shaping healthy behaviours; however, it currently appears to be dominated by screen time. A large proportion of young children do not adhere to the screen time recommendations, with the use of mobile screen devices becoming more common than fixed screens. Existing systematic reviews on correlates of screen time have focused largely on the traditional fixed screen devices such as television. Reviews specially focused on mobile screen media are almost non-existent. This paper describes the protocol for conducting a systematic review of papers published between 2009 and 2015 to identify the correlates of mobile screen media use among children aged 0–8 years. Methods: A systematic literature search of electronic databases will be carried out using different combinations of keywords for papers published in English between January 2009 and December 2015. Additionally, a manual search of reference lists and citations will also be conducted. Papers that have examined correlates of screen time among children aged 0–8 will be included in the review. Studies must include at least one type of mobile screen media (mobile phones, electronic tablets or handheld computers) to be eligible for inclusion. This study will identify correlates of mobile screen-viewing among children in five categories: (i) child biological and demographic correlates, (ii) behavioural correlates, (iii) family biological and demographic correlates, (iv) family structure-related correlates and (v) socio-cultural and environmental correlates. PRISMA statement will be used for ensuring transparency and scientific reporting of the results.Discussion: This study will identify the correlates associated with increased mobile screen media use among young children through the systematic review of published peer-reviewed papers. This will contribute to addressing the knowledge gap in this area. The results will provide an evidence base to better understand correlates of mobile screen media use and potentially inform the development of recommendations to reduce screen time among those aged 0–8 years.